Artificial Intelligence -Based Language Learning: Cake Application in Developing Speaking Skill - israeni iskandar; Nasriandi; Syahrir (Universitas Islam Negeri Palopo, 2025)
This study evaluates the effectiveness of CAKE application in improving the speaking skills of grade II students of SMA Negeri 6 Palopo. CAKE is an artificial intelligence (AI)-based English learning application with a speech recognition feature that provides immediate feedback on the user's pronunciation. The study used a pseudo quantitative experimental method with data collection techniques in the form of pre-test and post-test. The research sample was selected by simple randomization from the student population. The results showed that there was no statistically significant difference between the experimental class using the CAKE app and the control class using conventional methods based on the results of the independent T-test. However, the app still had a positive impact in improving students' speaking skills. Significant improvements were seen in the “Excellent” and “Moderate” categories in the experimental group compared to the control group. The motivational factor of the students also had an effect on the results of this improvement.